ANALISIS KEBERHASILAN PERUSAHAAN DAN LEMBAGA PENDIDIKAN DALAM PERSPEKTIF STRATEGI MANAJEMEN SUMBER DAYA - Hanifah Hanifah (STKIP NU Kabupaten Tegal, 2021)
Resources are very important for developments in the world of global organizations. The success of the organization is strongly influenced by resources and resource management strategies. The purpose of this article is that researchers will analyze the differences between corporate strategy and educational institutions and the adjustment of corporate strategies for educational institutions. The method of correlational research is carried out by referring to qualitative data from several successful cases and cases of failure in corporate organizations and educational institutions in terms of their resource strategies. Conceptually, the management strategy that is applied in companies can also be applied in educational institutions. In fact, the company's resource strategy is applied to obtain quality goods / services so as to get maximum profit. Meanwhile, resource management strategies in educational institutions are used to create better individual behavior. As for the implementation of management strategies in these two organizations, the adjustments needed lie in the organizational structure and function of each element of the organization.